ASSESSMENT OF HARIDRA DHUPAN IN FISTULECTOMY WOUND MANAGEMENT - Mandavkar Kalpana Chandrakant; Sachin.N.Pandhare; Jadhav K.Dnyaneshwar. (International Journal of Applied Ayurved Research, 2016)
Management of fistulectomy wound is challenge for surgeon. Due to moist anal region, continuous post-operative discharge from wound and daily bowel movement, the wound gets recurrently soiled and infected. Ultimately results into delayed and impaired wound healing. Dhupan kriya describe in Sushrut Smahita which act as analgesic and fumiside. With haridra dhupan we try to improve it and make it as antiseptic material even.in my services I treat many such cases, but this time I make scientific plan and carried out this project.To improvise the prognosis in terms of wound management, we decided to take up a clinical trial of 30 patients who have undergone partial fistulectomy with ksharsutra, fistulotomy or complete fistulectomy and were included in the study ‘Assessment of Haridra Dhupan in fistulectomy wound management.